Weakening Impact of Excessive Human Serum Albumin (eHSA) on Cisplatin and Etoposide Anticancer Effect in C57BL/6 Mice with Tumor and in Human NSCLC A549 Cells - Yang, Zhen; Zhou, Ting; Cheng, Yuanchi; Li, Mingming; Tan, Xianglin; Xu, Feng (Frontiers in Pharmacology, 2016)
Excessive human serum albumin (eHSA) impact on anticancer effects is inconsistent. We explored the outcome of cisplatin (DDP)/etoposide (VP-16) plus eHSA in vivo and in vitro. C57BL/6 mice with tumor were used to compare the efficacy of DDP/VP-16 alone and DDP/VP-16+eHSA. Blood albumin was measured to confirm whether eHSA elevate its level. Western blotting assay were used to measure the expression of ERCC1/TOP2A in tumor tissues. Cell proliferation, mRNA, and protein expression of ERCC1/TOP2A were also assayed to compare 2 groups in A549 cells. Furthermore we evaluated eHSA impact on cell proliferation in RNAi targeting ERCC1/TOP2A in A549 cells, respectively. eHSA reduced the anticancer effect of DDP/VP-16 without altering albumin level, increased protein expression of ERCC1/TOP2A, respectively in mice. Similarly, eHSA increased mRNA and proteins expression of ERCC1/TOP2A in A549 cells. In RNAi A549 cells, however, eHSA no longer weakened but enhanced the anticancer effect of DDP, while no longer altered the effect of VP-16. Our findings suggested that eHSA weaken the anticancer effect of DDP/VP-16 via up-regulating ERCC1/TOP2A expression, respectively. Further molecular mechanism studies are warranted to investigate whether eHSA is not conducive to lung cancer chemotherapy.